2023
DOI: 10.21037/tlcr-23-88
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0087378 intensifies the malignant behavior of non-small cell lung cancer cells in vitro by facilitating DDR1 via sponging miR-199a-5p

Abstract: Background Circular RNA hsa_circ_0087378 (circ_0087378) has been found to have different functions in different cancer types. However, its function in non-small cell lung cancer (NSCLC) remains unclear. This study revealed the effect of circ_0087378 on the malignant behavior of NSCLC cells in vitro to broaden the options for NSCLC treatment. Methods This study detected the expression of circ_0087378 in NSCLC cells via real-time quantitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Another study has shown that miR-199a-5p could regulate mesenchymal stem cell senescence in patients with idiopathic pulmonary fibrosis by regulating Sirt1/AMPK signaling pathway [ 12 ]. Previous studies have shown that certain circRNAs can bind competitively to miR-199a-5p to form miR-199a-5p response elements, thereby reducing their negative regulation of target genes, that is, influencing occurrence and development of non-small cell lung cancer through the competitive endogenous RNA (ceRNA) mechanism [ 13 , 14 ]. However, whether it is involved in the biological process of asthma through the ceRNA mechanism, affecting bronchial epithelial cells apoptosis and EMT, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown that miR-199a-5p could regulate mesenchymal stem cell senescence in patients with idiopathic pulmonary fibrosis by regulating Sirt1/AMPK signaling pathway [ 12 ]. Previous studies have shown that certain circRNAs can bind competitively to miR-199a-5p to form miR-199a-5p response elements, thereby reducing their negative regulation of target genes, that is, influencing occurrence and development of non-small cell lung cancer through the competitive endogenous RNA (ceRNA) mechanism [ 13 , 14 ]. However, whether it is involved in the biological process of asthma through the ceRNA mechanism, affecting bronchial epithelial cells apoptosis and EMT, remains unclear.…”
Section: Introductionmentioning
confidence: 99%